2002
DOI: 10.4049/jimmunol.169.7.3485
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Lethally Irradiated Adult Mice with Dominant Negative TGF-β Type II Receptor-Transduced Bone Marrow Leads to Myeloid Expansion and Inflammatory Disease

Abstract: TGF-β regulation of immune homeostasis has been investigated in the context of cytokine knockout (TGF-β null) mice, in which particular TGF-β isoforms are disrupted throughout the entire organism, as well as in B and T cell-specific transgenic models, but to date the immunoregulatory effects of TGF-β have not been addressed in the context of an in vivo mouse model in which multi-isoform TGF-β signaling is abrogated in multiple leukocyte lineages while leaving nonhemopoietic tissue unaffected. Here we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
0
39
2
Order By: Relevance
“…Such examples are abundant in the literature. Our own experience has indicated that transfer of non-tumor-specific CD8 + T cells to recipients will lead to widespread inflammatory disease (12,13). In the present study, the situation is more critical than the syngeneic systems, as the recipient is allogeneic to the transferred CD8 + T cells.…”
Section: Up-regulation Of Systemic and Local Levels Of Ifn-; And Il-2mentioning
confidence: 99%
See 3 more Smart Citations
“…Such examples are abundant in the literature. Our own experience has indicated that transfer of non-tumor-specific CD8 + T cells to recipients will lead to widespread inflammatory disease (12,13). In the present study, the situation is more critical than the syngeneic systems, as the recipient is allogeneic to the transferred CD8 + T cells.…”
Section: Up-regulation Of Systemic and Local Levels Of Ifn-; And Il-2mentioning
confidence: 99%
“…The ex vivo culture was done as described previously (14). Tumor-reactive CD8 + T cells were rendered insensitive to TGF-h by infection with ThRIIDN-green fluorescent protein (GFP) -containing retrovirus as described previously (12,13). Infection efficiency was assessed by GFP expression and flow cytometry and was always >90%.…”
Section: Experimental Animal and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…These investigators used transgenic mice with TGF-3 null expression targeted specifically to T cells. Subsequently, our study using transplant of TGF-pinsensitive bone marrow cells also demonstrated a total rejection of metastatic tumor cells 22 ' 23 However, in both studies, due to the non-specific nature of the immune cells, autoimmune disease eventually developed in the hosts. Results of our recent study have shown that adoptive transfer of tumorreactive TGF-p-insensitive CD8+ T cells were able to eradicate established lung metastasis of mouse prostate cancer cells, TRAMP-C2 24 .…”
Section: Discussionmentioning
confidence: 99%